APPLICATION OF CONSOLIDATED RESULTS OF THE VALUE OF LEARNING VOCATIONAL SCHOOL YAPENSA USINGMICROSOFT VISUAL BASIC 6.0 - Ristia Ningsih; Irfan, SKom, MMSI Irfan, SKom, MMSI (Jurnal Sistem Informasi, 2004)
In the data processing of student teachers' field of study requires a relatively long time to produce a report on the value of learning. The process of data entry in the percentage of value that must be right for each assessment component must also be approached through a precise calculation, for it required an application that helps in mengoleh and check the results report the value of learning so that each student can learn achievement. Therefore, application programs are used.